Hubungan Perilaku dengan Kecelakaan Kerja Pada Petani di Kecamatan Kotamobagu Barat - Akbar, Hairil; Rumaf, Fachry; Mokodompit, Putra Jufriyandi; Rismayani, Besse; Tutu, Christien Gloria (Universitas Wiralodra, 2025)
Occupational accidents are unintended and unforeseen events, not caused by deliberate actions, which may result in losses in terms of time, property, and even human life. Behaviors associated with occupational accidents among farmers include inadequate use of Personal Protective Equipment (PPE), non-compliance with safety procedures, errors in operating tools and machinery, lack of concentration, and negligence in following safety instructions for products such as pesticides. This study aims to examine the relationship between behavior (knowledge, attitudes, and practices) and occupational accidents among farmers in West Kotamobagu District. This research employed an analytical observational design with a cross-sectional approach. The study was conducted in West Kotamobagu District with a total population of 946 farmers. A sample of 90 farmers was selected using the Simple Random Sampling technique. Data analysis was carried out using the Chi-Square test. The findings revealed that knowledge (p = 0.000), attitude (p = 0.017), and practice (p = 0.007) were significantly associated with occupational accidents among farmers in West Kotamobagu District. Poor knowledge regarding occupational health and safety (OHS) and agricultural hazards, negative attitudes toward PPE usage, and undisciplined practices in its application were closely linked to the high incidence of occupational accidents among farmers. Adequate knowledge and awareness positively influence the adoption of safe behaviors, such as the proper and consistent use of complete PPE, thereby reducing the risk of occupational accidents.